2022
DOI: 10.1109/access.2022.3159695
|View full text |Cite
|
Sign up to set email alerts
|

Burning Graphs Through Farthest-First Traversal

Abstract: The graph burning problem is an NP-hard combinatorial optimization problem that helps quantify the vulnerability of a graph to contagion. This paper introduces a simple farthest-first traversalbased approximation algorithm for this problem over general graphs. We refer to this proposal as the Burning Farthest-First (BFF) algorithm. BFF runs in O(n 3 ) steps and has a tight approximation factor of 3−2/b(G), where b(G) is the size of an optimal solution. The main attribute of BFF is that it has a better approxim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Second, to understand the differences in the interfilament contacts among the clusters, we performed graph burning studies ( Bonato et al. , 2016 ; Garcia-Diaz et al. , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Second, to understand the differences in the interfilament contacts among the clusters, we performed graph burning studies ( Bonato et al. , 2016 ; Garcia-Diaz et al. , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…These results have been improved very recently. García-Díaz et al [10] have given a (3 − 2/b)-approximation algorithm where b is the burning number of the input graph. Mondal et al [17] have shown the graph burning problem to be APX-hard, even in a generalized setting where k = O(1) vertices can be chosen to initiate the fire at each step.…”
Section: Related Resultsmentioning
confidence: 99%
“…The optimization version of the problem also remains NP-hard for trees and graphs with disjoint paths [7]. Regarding arbitrary graphs, two approximation algorithms are reported in the literature; they have an approximation factor of 3 and 3 − 2/b(G), respectively [7,8]. There is a 2-approximation algorithm for trees, a 1.5-approximation algorithm for graphs with disjoint paths, and a 2-approximation algorithm for square grids [6,7].…”
Section: Definitionmentioning
confidence: 99%
“…Some of these proposals are based on centrality measures and binary search over the possible values of the burning number b(G). According to experimental results, these heuristics and approximation algorithms have an acceptable performance [4][5][6][7][8]. However, they do not guarantee to find optimal solutions.…”
Section: Introductionmentioning
confidence: 99%